2012
DOI: 10.1021/la301135z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Physical State of Phospholipid Monolayers on Protein Binding

Abstract: Langmuir monolayers were used to characterize the influence of the physical state of phospholipid monolayers on the binding of protein Retinis Pigmentosa 2 (RP2). The binding parameters of RP2 (maximum insertion pressure (MIP), synergy and ΔΠ(0)) in monolayers were thus analyzed in the presence of phospholipids bearing increasing fatty acyl chain lengths at temperatures where their liquid-expanded (LE), liquid-condensed (LC), or solid-condensed (SC) states can be individually observed. The data show that a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 33 publications
1
57
0
Order By: Relevance
“…Unfortunately, no measurements or theoretical deductions of the lateral pressure in the outer and cytoplasmic membranes of prokaryotes are available in literature then no comparison is possible with the here observed MIP value. Moreover, the N-L synergy factor (0.79, Table 1) is extremely high as compared to reported values for protein insertion into phospholipid monolayers (from 0.3 to 0.5) [24]. It can thus be concluded that the protein has a high affinity for the LPS interface between 18 and 30 mN/m and strikingly lysozyme insertion is almost not impacted by the lateral cohesion of the LPS molecules.…”
Section: The Affinity Of N-l For Lps Is Very High and Makes Possible mentioning
confidence: 51%
See 2 more Smart Citations
“…Unfortunately, no measurements or theoretical deductions of the lateral pressure in the outer and cytoplasmic membranes of prokaryotes are available in literature then no comparison is possible with the here observed MIP value. Moreover, the N-L synergy factor (0.79, Table 1) is extremely high as compared to reported values for protein insertion into phospholipid monolayers (from 0.3 to 0.5) [24]. It can thus be concluded that the protein has a high affinity for the LPS interface between 18 and 30 mN/m and strikingly lysozyme insertion is almost not impacted by the lateral cohesion of the LPS molecules.…”
Section: The Affinity Of N-l For Lps Is Very High and Makes Possible mentioning
confidence: 51%
“…The synergy factor as introduced by Boisselier et al [24] and Calvez et al [23] is also higher with DH-L than with N-L, and is positive for both proteins (0.85 and 0.79, respectively; Table 1) [24]. Oppositely, the Δπ 0 are similar for N-L and DH-L (8.75 and 9.10 mN mN/m, respectively; Table 1).…”
Section: Affinity Of Lysozyme For Lps Monolayersmentioning
confidence: 78%
See 1 more Smart Citation
“…It is also interesting to compare the behavior of the peptide in the presence of unsaturated, polyunsaturated as well as saturated phospholipids. Indeed, the different physical states of these phospholipids could drive specificity of peptide binding such as previously observed for different proteins [205,327]. The specific binding of a peptide to a saturated phospholipid could also suggest that this peptide is located in rafts since these structures contain a large percentage of this type of fatty acyl chain (for a review, see [329][330][331][332]).…”
Section: Determination Of the Maximum Insertion Pressure And Synergy mentioning
confidence: 89%
“…It is meaningful to calculate the uncertainty of the MIP and synergy data, which allows to make proper conclusions. This experimental error must absolutely be calculated, as previously described [116,205,327,328]. The data are otherwise very difficult to properly interpret.…”
Section: Determination Of the Maximum Insertion Pressure And Synergy mentioning
confidence: 99%